2014
DOI: 10.1002/cam4.273
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant promoter methylation of PPP1R3C and EFHD1 in plasma of colorectal cancer patients

Abstract: Aberrant DNA methylation is a common epigenetic alteration involved in colorectal cancer (CRC). In our previous study, we performed methylated DNA immunoprecipitation-on-chip analysis combined with gene re-expression analysis by 5-aza-2′-deoxycytidine treatment, to identify methylation genes in CRC genome widely. Among these genes, 12 genes showed aberrant hypermethylation frequently in >75% of 149 CRC samples but did not in normal samples. In this study, we aim to find out any of these methylation genes to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 29 publications
4
31
0
Order By: Relevance
“…Smith et al previously reported that in cDNA microarray analysis STOX2 expression is associated with prognosis in colon cancer, and our results are largely consistent with their findings [ 31 ]. Conversely, CpG island hypermethylation of STOX2 promoter region reportedly reduces STOX2 expression in colon adenoma and adenocarcinoma [ 32 , 33 ]. However, methylation of STOX2 was not observed in OSCC cells (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Smith et al previously reported that in cDNA microarray analysis STOX2 expression is associated with prognosis in colon cancer, and our results are largely consistent with their findings [ 31 ]. Conversely, CpG island hypermethylation of STOX2 promoter region reportedly reduces STOX2 expression in colon adenoma and adenocarcinoma [ 32 , 33 ]. However, methylation of STOX2 was not observed in OSCC cells (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…EFHD1 (EF-hand domain family member D1) encodes a calcium-binding protein involved in mitosis, synaptic transmission, and cytoskeletal rearrangement [ 67 ]. In the present systematic review, methylation of EFHD1 had 79% sensitivity and 22% specificity for CRC in plasma [ 32 ]. When combined with the analysis of PPP1R3C methylation, sensitivity was 53% and specificity reached 96% [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present systematic review, methylation of EFHD1 had 79% sensitivity and 22% specificity for CRC in plasma [ 32 ]. When combined with the analysis of PPP1R3C methylation, sensitivity was 53% and specificity reached 96% [ 32 ]. No patients with adenoma were included in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we demonstrated that several other phosphatases (PPP1R3C, INPP4B, FBP1, PTPRT, MTMR9, and CANT1) are underexpressed in ER-negative compared to those in ER-positive breast cancers. The PPP1R3C gene is hypermethylated in colorectal cancer (CRC) [ 47 ], and is a candidate tumor suppressor gene in melanoma and is inactivated through promoter methylation [ 48 ]. Gewinner et al have shown that INPP4B regulates the PI3 K pathway and that its gene is located in a region frequently deleted in both breast cancer cell lines and high-grade breast tumors [ 49 51 ].…”
Section: Discussionmentioning
confidence: 99%